Insights into energy transfer pathways between the exciplex host and fluorescent guest: attaining highly efficient 710 nm electroluminescence. Issue 17 (3rd April 2020) - Huang, Chun-Ying; Ho, Ssu-Yu; Lai, Chien-Hsun; Ko, Chang-Lun; Wei, Yu-Chen; Lin, Jia-An; Chen, Deng-Gao; Ko, Tzu-Yu; Wong, Ken-Tsung; Zhang, Zhiyun; Hung, Wen-Yi; Chou, Pi-Tai
Abstract : Insight has been gained into the energy transfer pathways between the exciplex host and NIR fluorescence chromophores. Abstract : Energy transfer between the exciplex host and fluorescent guest is a demanding process for attaining high-performance organic light-emitting diodes (OLEDs), particularly in the near-infrared (NIR) region, and insight into the dynamics of energy transfer has been elusive. In this study, new deep-red/NIR chromophores, NOz-TPA and NOz- t -TPA where NOz and TPA denote naphthobisoxadiazole and triphenylamine, respectively, have been developed with an electron donor–acceptor–donor (D–A–D) configuration. The optimized 1 wt% doped films for NOz-TPA and NOz- t -TPA blended with the Tris-PCz :CN-T2T (1 : 1 in molar ratio) exciplex host showed similar deep red/NIR emissions with photoluminescence quantum yields (PLQY) of 42 (680 nm) and 28%, (709 nm), respectively. Comprehensive time-resolved measurements and dynamics analyses revealed significant differences in the energy transfer pathways, i.e. Förster versus Dexter-type energy transfer between the exciplex host and the fluorescent guest, in which the introduction of bulky tert -butyl groups in the NOz- t -TPA doped film greatly suppressed the Dexter-type energy transfer pathway. Despite the lower PLQY, the analytical simulation predicted NOz- t -TPA to be a better candidate for realizing highly efficient electroluminescence. Confirmation was provided by the performance of the NOz- t -TPA -doped OLED, showing an external quantum efficiency (EQE) of 6.6% with peak wavelength at 710 nm, which is among the best records for the metal-free NIR OLEDs around 710 nm. Insight into energy transfer pathways thus plays a pivotal role in achieving the high-performance OLEDs that incorporate the exciplex host and fluorescent guest.